(untitled) (Cadernos de Sociomuseologia, 2009)
In the early 90’s, Mario Moutinho launched the concept of social museology, idea which symbolizes much of the updates taken place in the field of museology during the past years. Created as a framework for the newly implemented museology courses at the Universidade Lusófona in Lisbon, the concept of social museology translates, according to Moutinho (1993), considerable part of the efforts in adapting museology to contemporary society conditionalisms56. It refers to the opening of museological structures to the milieu and their organic relation with the social context that brings them to life. The notion of social museology, as well as the appreciation of the context in which it was created, serve as departure to analyse two aspects that characterize the state of affairs between museology and community development today -relationship marked by a slow convergence that has become more solid since the decade of 90, period when proposals concerning contributions to development clearly began to extrapolate the circle of the new museology and integrate the broader field of museology. The first aspect refers to the relations of museums (and the museological field as a whole) with contemporary society and the second to an approximation between the so-called new and traditional museology.